Amish country ambush - Lynn, Dana R. (Lynn, Dana R. Amish country justice., 2018)
After police dispatcher Elise St. Clair<U+2019>s home is invaded by her murderous brother-in-law, her nephew is hidden in Amish Country by her cleaning lady. Now relying on police officer Ryan Parker is Elise<U+2019>s only hope of reuniting with the child<U+2026>and evading the killer. And Elise and Ryan quickly discover their temporary partnership has long-term potential<U+2014>if they can stay alive.